Sporting memories, dementia care and training staff in care homes. Issue 1 (9th January 2017) - Clark, Michael; Murphy, Charlie; Jameson-Allen, Tony; Wilkins, Chris
Abstract : Purpose: The purpose of this paper is to describe the findings from a pilot and a follow-on study in which care assistants in care homes were trained to use sporting memories work to better help and engage with residents with dementia and low mood. Care homes have to support increasingly more fragile people and often the range of activities in the homes do not offer the best engagement between residents and staff to benefit the residents. This is for reasons of time to run activities in a busy home, and because of the need to find financially viable means of running a range of activities. Care assistants in care homes are a group of non-professionally educated workers and are often overlooked for training beyond basic health and safety training to help them improve their work and the care they provide. This work sought to explore whether sporting memories work was viable as an activity to offer in care homes via the training of care assistants. Design/methodology/approach: The paper discusses the evidence from a pilot and then follow-on project in care homes in one city area. In the pilot observation was made of a training session and follow up interviews were undertaken with care home managers to see how the implementation of sporting memories was going. In the follow-on project the support to those undertaking the training was modified to include three learning network sessions. Data were collected on the experience of participants and their use of sporting memories work. Findings: The findings were that care assistants could be trained in using sporting memories work and they often found it easy to use and fulfilling for them and people they cared for. This was despite the care assistants who participated often not having much interest in sports and little experience in this kind of work. However, practical barriers to maintaining the use of sporting memories work did remain. Research limitations/implications: The evidence to date is of case studies of training staff in care homes in the use of sporting memories work, which provides good grounding for proof of the concept and key issues, but further research is needed on the costs and impacts of sporting memories work in care homes. The lack of direct feedback about experiences of care home residents of sporting memories work and its impact on them is a further limitation. Practical implications: Sporting memories work is a flexible and readily adoptable intervention to engage older people in care homes and the evidence to date is that care assistants in care homes can be trained to use this approach to engaging older people. Practical challenges still remain to using sporting memories work in care homes, notably the issue of time for staff to do the work, but it is an approach for care homes to have available to them to match up to the interests of residents. Social implications: Sporting memories work can be an important part of meeting some of the challenges society faces with an ageing population profile and to enhancing the care home environment and care assistants can be trained to use the approach. Originality/value: This is the first paper to discuss training care home staff in the use of sporting memories work.